Associations between Trans Fatty Acid Consumption and Colon Cancer among Whites and African Americans in the North Carolina Colon Cancer Study I - Vinikoor, Lisa C (2009)
Disparities in incidence and mortality rates of colon cancer exist between Whites and African Americans. Prior studies examined the association between trans fatty acid consumption and colorectal cancer, but none assessed this possible relationship within a large study population of African Americans and Whites. Using data from a population-based case-control study in North Carolina, we investigated this association with attention to possible racial differences. Cases and matched controls were queried on demographic characteristics, lifestyle factors, medical history, and diet. Cases reported higher daily consumption (grams/day) of trans fatty acids [mean 5.9 (SD 2.9) and median 5.5 (IQR 3.8-7.5)] compared to controls [mean 5.2 (SD 2.4) and median 4.7 (IQR 3.5-6.4)]. Energy-adjusted trans fatty acid consumption was not associated with colon cancer. Compared to participants in the lowest quartile of consumption, those in the highest quartile had an adjusted odds ratio of 1.01 (95% confidence interval 0.69, 1.49) for Whites and 0.99 (95% confidence interval 0.61, 1.62) for African Americans. No association was found between increased consumption of trans fatty acid and specific tumor location (proximal or distal colon). In conclusion, trans fatty acid consumption is not associated with colon cancer and does not contribute to disparities in colon cancer rates.